Total synthesis of isatisindigoticanine H - Wabale, Krishna R.; Ramana, Chepuri Venkata (Synthesis-Stuttgart, 2025)
The first total synthesis of the naturally occurring isatisindigoticanine H has been completed by employing D-mannitol as the chiral pool precursor to install the requisite stereochemistry of the natural product. Construction of the thiazole unit by dehydrative cyclization of a alpha-halo ketone with thiourea followed by Sandmeyer's reaction and subsequent nucleophilic addition of lithiated bromothiazole to the Weinreb amide are the key reactions employed in this regard.
Keywords: Chiral pool approach; Indothiazinone; Isatisindigoticanine H; Sandmeyer reaction; Total synthesis